2020
DOI: 10.22207/jpam.14.3.01
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the World with Co-Morbidities of Heart Disease, Hypertension and Diabetes

Abstract: Newly emerging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) pandemic has now spread across the globe in past few months while affecting 26 million people and leading to more than 0.85 million deaths as on 2nd September, 2020. Severity of SARS-CoV-2 infection increases in COVID-19 patients due to pre-existing health co-morbidities. This mini-review has focused on the three significant co-morbidities viz., heart disease, hypertension, and diabetes, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 131 publications
1
25
0
Order By: Relevance
“…According to epidemiological data, most deaths from COVID-19 are concentrated in the elderly with common comorbidities such as hypertension, diabetes or obesity (62)(63)(64). In general, this group of individuals has a higher prevalence of zinc deficiency (65)(66)(67)(68)(69), given that aging is associated with a progressive decline in zinc status in the body due to several factors, including reduced food intake, decreased nutrient absorption efficiency and use of medications (70,71).…”
Section: Nutrients and Viral Infections Zincmentioning
confidence: 99%
“…According to epidemiological data, most deaths from COVID-19 are concentrated in the elderly with common comorbidities such as hypertension, diabetes or obesity (62)(63)(64). In general, this group of individuals has a higher prevalence of zinc deficiency (65)(66)(67)(68)(69), given that aging is associated with a progressive decline in zinc status in the body due to several factors, including reduced food intake, decreased nutrient absorption efficiency and use of medications (70,71).…”
Section: Nutrients and Viral Infections Zincmentioning
confidence: 99%
“…Increased blood levels of markers of cardiometabolic dysfunction, such as creatinine kinase, aspartate aminotransferase and cardiac troponin 1 have been detected in people who died from COVID-19, compared to those who recovered ( 131 ). These observations may be linked to complications of cardiovascular disease induced by COVID-19, such as cardiomyocyte necrosis, hypertension and coronary plaque instability ( 131 ) Other hypothesized mechanisms that could increase risk of COVID-19 severity in people with cardiometabolic disease include: diminished lung function; pre-existing lung damage (including lipofibrosis in lungs ( 132 ); impaired pancreatic beta-cell function ( 131 ); poor responsiveness/capacity for mechanical ventilation; impaired fibrinolysis capacity and pulmonary perfusion; dysregulated endocrine function; and, gut dysbiosis ( 133 , 134 ). Non-medical factors that associate with increased risk include poverty and over-crowded housing conditions that likely reduce the capacity of individuals to undertake social isolation recommendations, and promote viral spread ( 125 ).…”
Section: Could Uv Light Have Harmful or Beneficial Effects On Covid-1mentioning
confidence: 99%
“…Early epidemiological data revealed that SARS-CoV-2 is more likely to affect older males with comorbidities, and can result in severe and even fatal respiratory diseases such as ARDS and multiple organ failure ( Chen et al, 2020 ). Reported comorbidities in infected patients that require hospital admission include cardiovascular disease/heart disease, diabetis mellitus, chronic respiratory disease, hypertension and cancer ( Butchi et al, 2011 ; Arumugam et al, ; Huang et al, 2020 ; Wu and McGoogan, 2020 APR 7). Obesity, has been positioned as common denominator of impaired metabolic health, respiratory dysfunction, cardiovascular disease and diabetes mellitus in the severe course of COVID-19 ( Stefan et al, 2020 ).…”
Section: Multidisciplinary Clues That Reason the Proposed Role For Tlmentioning
confidence: 99%